Washback effect of the Celpe-Bras exam in teachers’ education practices at a Brazilian institute abroad - Vargas da Costa, Everton (BELT - Brazilian English Language Teaching Journal, 2018)
This paper aims to describe and analyze the washback effect of Celpe-Bras exam in the Portuguese as additional language teachers’ education practices in a Brazilian institute abroad. Part of the framework adopted understands that the pedagogical work of teachers is organized around dialogue and collaboration through which participants learn how to teach while interacting with their peers (Pérez Gómez, 1995; Nóvoa, 1995; FCC, 2011). At the institute, the washback effect of the Celpe-Bras exam contributes to those interactions by resizing the Portuguese language teaching and learning practices. Participant observation and the ethnographic analysis of the data enables the discussion about the local dimension of washback effects of Celpe-Bras, involving micro and macro social aspects such as acquisition of specific terminology and understanding of the political project underlying the exam. Moreover, by participating and engaging in pedagogical meetings, teachers improve their abilities dealing with Celpe-Bras’ construct and pave pedagogical trajectories as more experienced professionals at the institute.